The Effects of Electricity Consumption and Economic Growth on Carbon Dioxide Emission - Shaari, Mohd Shahidan; Abdul Razak, Nor Azam; Hasan Basri, Bakti (International Journal of Energy Economics and Policy, 2017)
This study aims to investigate the effects of electricity consumption and economic growth on carbon dioxide emission in Malaysia from 1971 to 2013. The ARDL bound testing approach was employed and the results show that there are some effects of electricity consumption and economic growth on carbon dioxide emission in the long run. However, in the short run, the results show that there is no significant effect of electricity consumption and economic growth on carbon dioxide emission in Malaysia. Therefore the government should formulate several policies to ensure that the country can boost economic growth without any deleterious effect on the environment. Keywords: electricity consumption, economic growth, carbon dioxide emission JEL Classifications: Q11, Q43